Migration of surface excitations in highly-excited nanosystems probed by intense resonant XUV radiation. (13th November 2015) - Katzy, R; LaForge, A C; Ovcharenko, Y; Coreno, M; Devetta, M; Fraia, M Di; Drabbels, M; Finetti, P; Lyamayev, V; Mazza, T; Mudrich, M; O'Keeffe, P; et al.
Abstract: Ionization dynamics of resonantly excited helium nanodroplets have been studied by intense XUV light. By doping the nanodroplets with atoms that either attach to the surface or submerge into the center of the droplet, one can study the dynamics of excitation and ionization through the droplet. When resonantly exciting the droplet, we observe a strong ionization enhancement for atoms attached to the surface. On the other hand, atoms embedded inside the nanodroplet are less efficiently ionized. We attribute this effect to an ultrafast energy transfer to the surface of the droplet and subsequent Penning ionization of the surface-bound dopant.